Electronic, optical, and spectroscopic analysis of TBADN organic semiconductor: Experiment and theory - Orek, Cahit; Gunduz, Bayram; Kaygili, Omer; Bulut, Niyazi (Elsevier, 2017)
In this study, the electronic, optical and spectroscopic properties of 2-tert-Butyl-9,10-di(naphth-2-yl) anthracene (TBADN) semiconductor in different solvents were investigated by experimentally and computationally. Obtained theoretical and experimental UV VIS spectra of the TBADN were found to be quite in good agreement and can be controlled with various solvents. Refractive index values of the TBADN semiconductor in different solvents were experimentally measured and calculated theoretically. Finally, the FTIR spectra of the TBADN organic semiconductor in different solvents were investigated by theoretical and experimental methods. It was found that the band gap is sensitive to the concentration of the solute. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Anthracene derivative; Organic semiconductors; Gaussian 09; B3LYP; TD-DFT; HOMO-LUMO